Economic Growth Rates Based on the Agriculture Sector Comparative Analysis - Djuanda Hatta (Universitas Gorontalo, 2023)
Finding potential sub-sectors and products in the City District of North Kalimantan Province is the goal of this research. To determine the contribution of the sub-sector, the method used is sub-sector mapping using the Overlay and Klassen Typology derived from LQ (Location Question) analysis to determine the comparative adventages, GRM (Growth Ratio Model) to determine the potential product and subsector, and SS (Shift Share) to determine the competitiveness of the sector. The results of the study show that each district/city in North Kalimantan Province has regional sub-sectors and products that are superior, potential and competitive and become their respective characteristics. As a result, it will become a policy suggestion for prospective sector growth in each location.